Comparison of contemporary troponin assays with the novel biomarkers, heart fatty acid binding protein and copeptin, for the early confirmation or exclusion of myocardial infarction in patients presenting to the emergency department with chest pain. Issue 2 (22nd November 2013) - Collinson, Paul; Gaze, David; Goodacre, Steve
Abstract : Objective: To examine the diagnostic accuracy of novel biomarkers of myocardial injury and troponin assays for diagnosis of myocardial infarction. Methods: 850 patients randomised to the point-of-care testing arm of the Randomised Assessment of Panel Assay of Cardiac markers (RATPAC) study in six emergency departments of low-risk patients presenting with chest pain were studied. Blood samples were obtained on admission and 90 min from admission. Myocardial infarction was defined by the universal definition of myocardial infarction. The following diagnostic strategies were compared by receiver operator characteristic curve analysis and comparison of area under the curve: individual marker values and the combination of presentation heart fatty acid binding protein (HFABP) and copeptin with troponin. Results: 68 patients had a final diagnosis of myocardial infarction. Admission samples were available from 838/1132 patients enrolled in the study. Areas under the curve were as follows (CIs in parentheses): cardiac troponin I (cTnI) Stratus CS 0.94 (0.90 to 0.98), cTnI Beckmann 0.92 (0.88 to 0.96), cTnI Siemens ultra 0.90 (0.85 to 0.95), cardiac troponin T high sensitivity 0.92 (0.88 to 0.96), HFABP 1 0.84 (0.77 to 0.90) copeptin 0.62 (0.57 to 0.68). HFABP and copeptin were diagnostically inferior to troponin. The combination of HFABP (at the 95th percentile) and troponin (at the 99th percentile) increased diagnostic sensitivity. Conclusions: High-sensitivity cardiac troponin is the best single marker. Addition of HFABP to high-sensitivity troponin increased diagnostic sensitivity. Additional measurement of copeptin is not useful in the chest pain population.